Climate Change and Livestock Production - Kumar, Puneet; Singh, G.; Maurya, V. P.; Sarkar, M.; Tiwari, A. K. (Indian Farming, 2015)
Although experimental studies have been conducted on the effects of season and climate on production, reproduction and other physiological parameters of animals. Long term systematic studies in open natural environment on effects of different biotic and abiotic stressors are needed on animal production in different climatic conditions in relation to climate change. Some models need to be prepared to predict livestock productivity in relation to THI variability. Index of more heat tolerant individuals within a breed will help for further breeding programmes. Traits or factors in indigenous livestock making them resilient to climate change in relation to diseases needs to be focused.